Under Armour conquering the sportswear market - Pires, Margarida Carlos Nobre (2022)
The current work project aims to calculate the fair value of Under Armour's stock on December 31, 2022. To reach the final recommendation, two valuation methods were used: Discounted Cash Flow (DCF) method and multiples. The DCF result reached a target price of $27.07 per share, indicating that Under Armour is undervalued by the market when compared to the current price of $24.45 per share as of December 16, 2021. The valuation by Multiples also confirmed that UA is currently undervalued. Therefore, the recommendation of Under Armour’s equity valuation is a BUY recommendation.